The influence of undertreated chronic pain in a national survey: Prescription medication misuse among American indians, Asian Pacific Islanders, Blacks, Hispanics and whites - Michelle Johnson-Jennings, PhD, EdM; Bonnie Duran, PhD; Jahn Hakes, PhD; Alexandra Paffrath, PharmD; Meg M. Little, EdD (Elsevier, 2020)
Objective: Disparities in the assessment and treatment of chronic pain among racial/ethnic may lead to self-treatment for undertreated pain. This study examines whether pain intensity among US racial/ethnic groups' influences rates of psychotherapeutic prescription drug misuse. Methods: Data included civilian, non-institutionalized adults (age 18-99 years) residing in the United States (n = 34,653) from Waves 1 and 2 of the National Epidemiological Survey on Alcoholism and Related Conditions (NESARC; 2004-2005). The primary outcome variable was prescription drug misuse/PDM (i.e., use without a prescription or other than as prescribed) including tranquilizers, sedatives, stimulants, or opioids. Predictor variables included self-reported race/ethnicity (American Indian, Black, Hispanic, or White) and pain intensity. Data were analyzed in 2019. Results: Overall, White and Hispanic participants' pain intensity had a significantly curvilinear relationship with frequency of prescription medication (p < 0.01). PDM rose with pain intensity until pain levels reached "severe," then PDM rates fell, not significantly differing from the "no pain" levels (χ2(1) = 0.65, p = 0.42). PDM rates for Black participants remained lowest of all other racial/ethnic groups and plateaued with increasing pain intensity. Conclusions: Our results indicate that undertreated chronic pain may drive rates of PDM among varying racial/ethnic groups. Providing equitable assessment and treatment of pain intensity remains critical. Additional research is needed to examine provider decision-making and unconscious bias, as well as patient health beliefs surrounding perceived need for prescription pain medications.